Clinical and functional features and quality of life in depressive disorders in patients undergoing pulmonary thromboendarterectomy - O. V. Kamenskaya; A. S. Klinkova; I. Yu. Loginova; S. S. Porotnikova; I. I. Volkova; V. N. Lomivorotov; A. M. Chernyavskiy (Российский кардиологический журнал, 2022)
Aim. To conduct a comparative analysis of clinical and functional parameters and quality of life (QoL) in patients with chronic thromboembolic pulmonary hypertension (CTEPH), depending on the presence of a depressive disorder in long-term postoperative period.Material and methods. The study included 182 patients with CTEPH in the long term after surgery. Depending on the Patient Health Questionnaire 9 ( PHQ-9) data, all patients were divided into 2 groups: the 1st group — patients without depressive syndrome in the long-term postoperative period, the 2nd — patients with depressive syndrome. A comparative assessment of the initial clinical and functional characteristics, as well as QoL was carried out using the SF-36 questionnaire in both groups of patients. In patients who had a coronavirus disease 2019 (COVID-19), a comparative assessment using the Post-COVID-19 Functional Status (PCFS) scale was carried out.Results. Clinically relevant depressive syndrome in patients with CTEPH in the long term after surgery was registered in 25,3% of cases. In the 2nd group of patients, prior myocardial infarction (p=0,02), concomitant chronic cerebrovascular disease (p=0,01), as well as moderate and severe post-COVID-19 functional limitations according to the PCFS scale (p=0,004) were significantly more often recorded compared with the 1st group. In the 2nd group of patients, the level of QoL in almost all parameters was significantly lower in comparison with the 1st group (p<0,05). Decreased QoL (score <40) in the 2nd group concerned numerous parameters, including the physical and mental health components. In the 1st group of patients, reduced QoL was observed only in some physical parameters.Conclusion. The group of patients with CTEPH with depressive syndrome in the long-term postoperative period was characterized by a higher incidence of concomitant chronic cerebrovascular disease and a history of myocardial infarction compared with patients without depressive disorders. In the group of patients with depressive disorders, moderate and severe post-COVID-19 functional limitations according to the PCFS scale were more often observed. Depressive disorders in patients with CTEPH in the long-term postoperative period were accompanied by significantly reduced QoL parameters. Patients experienced the greatest difficulties both during normal daily activities and in professional activities.